THE EFFECT OF SERVICE QUALITY AND BRAND IMAGE ON CUSTOMER LOYALTY WITH CUSTOMER SATISFACTION AS AN INTERVENING VARIABLE - Suhad, Suhad; Iswati, Heni (Universitas Islam Negeri Ar-Raniry Banda Aceh, 2024)
This study aims to analyze the effect of service quality and brand image on customer satisfaction and its impact on customer loyalty at PT Asuransi Jasindo Syariah. Service quality and brand image have a very important role in building positive relationships with customers, which can increase customer satisfaction and loyalty.This research method involves surveying customers of PT Asuransi Jasindo Syariah to collect primary data. The sampling technique was carried out using purposive sampling method, and the data were analyzed using path analysis to measure the relationship between these variables. The results of data analysis show that service quality and brand image significantly affect customer satisfaction. In addition, customer satisfaction is also proven to have a significant impact on customer loyalty.The implication of these findings is that PT Asuransi Jasindo Syariah needs to continue to improve the quality of service to its customers and strengthen its brand image in order to maintain and increase customer satisfaction, which in turn will contribute to increased customer loyalty. Company management needs to understand the importance of maintaining positive relationships with customers and focus on developing strategies to improve service quality and strengthen brand image in order to achieve the company's long-term goals.